Thunderhead - Shusterman, Neal (New York : Simon & Schuster BFYR, 2018)
"The Thunderhead is the perfect ruler of a perfect world, but it has no control over the scythedom. A year has passed since Rowan has gone off grid. Since then he has become an urban legend, a vigilante snuffing out corrupt scythes in a trial by fire. His story is told in whispers across the continent. As Scythe Anastasia, Citra gleans with compassion and openly challenges the ideals of the 'new order.' But when her life is threatened and her methods questioned, it becomes clear that not everyone is open to change."--
Keywords: Death -- Juvenile fiction; Murder -- Juvenile fiction; Vigilantes -- Juvenile fiction; Political corruption -- Fiction; Young adult fiction; Science fiction